Lithium battery negative electrode material for high temperature and high rate and preparation method thereof

The porous carbon-based lithium battery negative electrode material was prepared by using silicon-containing polyurea polymer as the carbon precursor and high-temperature carbonization treatment, which solved the problem of insufficient specific capacity and rate performance of existing materials, and achieved higher electrochemical performance and high-temperature resistance.

CN119569032AActive Publication Date: 2025-03-07JIANGSU LIANGNENG POWER TECH CO LTD +1
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411782098.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-05
Publication Date
2025-03-07
Estimated Expiration
2044-12-05

AI Technical Summary

Technical Problem

The specific capacity and rate performance of the negative electrode materials of existing lithium-ion batteries are relatively low, making it difficult to meet the application needs of high temperature and high rate.

Method used

A porous carbon-based lithium battery negative electrode material with a porous structure and a high specific surface area was prepared by high-temperature carbonization treatment.

Benefits of technology

The specific capacity, rate performance and Coulomb efficiency of the lithium battery negative electrode material are improved, and the first charge and discharge specific capacity and Coulomb efficiency are still shown in high temperature conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005173019870000021
    Figure BDA0005173019870000021
  • Figure BDA0005173019870000081
    Figure BDA0005173019870000081
  • Figure BDA0005173019870000082
    Figure BDA0005173019870000082
Patent Text Reader

Abstract

The invention relates to the technical field of lithium ion batteries, and discloses a high-temperature and high-rate lithium battery negative electrode material and a preparation method thereof. The preparation method comprises the following steps: reacting di (3, 6-diaminocarbazole) dimethylsilane with diisocyanate to obtain a silicon-containing polyurea polymer, then blending the silicon-containing polyurea polymer with potassium hydroxide, and carbonizing to obtain the porous carbon-based lithium battery negative electrode material for high temperature and high rate. The porous carbon-based negative electrode material disclosed by the invention contains active nitrogen-doped structures such as pyrrole nitrogen and graphite nitrogen, so that the electrochemical properties such as conductivity and specific capacity of the carbon-based negative electrode material can be improved. Meanwhile, the silicon element forms active components such as nano silicon and silicon carbide in the high-temperature carbonization process, and the active components are uniformly dispersed in a carbon matrix, so that the electrochemical performance such as specific capacity is further improved, and the negative electrode material shows higher charge-discharge specific capacity, coulombic efficiency and rate capability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a negative electrode material for a high-temperature and high-rate lithium battery and a preparation method thereof. Background Art

[0002] Lithium-ion batteries have high energy density, high charging efficiency, wide operating temperature range, and no memory effect. They are widely used in new energy vehicles, portable electronic products, and other fields. The negative electrode of commercial lithium-ion batteries is graphite material, which has a low theoretical capacity, limiting the practical application of lithium-ion batteries. The development of high-performance negative electrode active materials is a research hotspot.

[0003] The current lithium-ion battery negative electrode active materials mainly include porous carbon negative electrode, silicon-based negative electrode, metal oxide negative electrode, metal sulfide negative electrode, etc. Among them, the porous carbon negative electrode has the advantages of large specific surface area, high cycle stability, good temperature resistance, and diverse preparation methods. In addition, the carbon matrix is ​​doped with heteroatoms such as nitrogen, sulfur, and phosphorus to improve the electrochemical performance of carbon negative electrode materials.

[0004] Silicon-based negatives mainly include nano-silicon, silicon dioxide, silicon carbide and other negative electrodes, which have higher theoretical specific capacity and are a kind of lithium-ion battery negative electrode material with great application prospects. The invention patent with announcement number CN110752352B discloses a preparation method of a boron-nitrogen-doped polymer-assisted synthesis of carbon-coated silicon negative electrode materials, using nano-silicon powder, nitrogen-containing polymer monomers, boron-containing compounds, initiators, etc. as raw materials to obtain a nitrogen-containing polymer-silicon precursor. After high-temperature calcination, the obtained boron-nitrogen-doped carbon-coated silicon negative electrode material has the advantages of high coulombic efficiency. Compared with the invention, the present invention uses silicon-containing polyurea polymer as a carbon precursor, and the obtained porous carbon-based lithium battery negative electrode material has higher specific capacity, rate performance and coulombic efficiency. Summary of the invention

[0005] Technical problem to be solved: The present invention provides a porous carbon-based lithium battery negative electrode material with large specific capacity and high rate performance.

[0006] Technical solution: A method for preparing a negative electrode material for a high-temperature and high-rate lithium battery, comprising the following steps:

[0007] S1. Add N,N-dimethylformamide, di(3,6-diaminocarbazole)dimethylsilane, diisocyanate, and dibutyltin dilaurate into a reaction container, heat to 60-75° C., stir and react for 3-5 hours, add water to the solution, filter, wash with ethanol, and dry to obtain a silicon-containing polyurea polymer.

[0008] S2. Grind the silicon-containing polyurea polymer, mix it with potassium hydroxide, and place it in a tubular furnace. Pass nitrogen and heat it to 850-950°C at a heating rate of 5-10°C / min. Carbonize it for 2-3 hours. Grind it after cooling, wash it with water, and dry it to obtain a negative electrode material for a lithium battery for high temperature and high rate use.

[0009] Preferably, the ratio of di(3,6-diaminocarbazole)dimethylsilane, diisocyanate, and dibutyltin dilaurate in S1 is 1 mol:(3.8-4.2) mol:(0.02-0.03) mol.

[0010] Preferably, the diisocyanate is toluene-2,4-diisocyanate or 4,4'-methylenebis(phenylisocyanate).

[0011] Preferably, the ratio of the silicon-containing polyurea polymer to potassium hydroxide in S2 is 1 g:(2.5-4) g.

[0012] Preferably, the preparation method of bis(3,6-diaminocarbazole)dimethylsilane is as follows: add a solvent, 3,6-dinitro-9H-carbazole, dropwise add a n-butyl lithium hexane solution at -78°C, stir and activate for 2-3h, then dropwise add dichlorodimethylsilane, react at room temperature for 12-18h, rotary evaporate, wash with methanol, add the product to ethanol, add a palladium carbon catalyst, a hydrazine hydrate solution, heat to 75-85°C, condense and reflux for 5-8h, rotary evaporate after filtering, separate by silica gel column chromatography, and gradient elute with ethyl acetate and petroleum ether eluent to obtain bis(3,6-diaminocarbazole)dimethylsilane. The reaction formula is:

[0013]

[0014] Preferably, the ratio of 3,6-dinitro-9H-carbazole, n-butyl lithium and dichlorodimethylsilane is (2-2.4) mol: (2.6-3.2) mol: 1 mol.

[0015] Preferably, the solvent is tetrahydrofuran or toluene.

[0016] The present invention also provides a negative electrode material for a high-temperature and high-rate lithium battery prepared according to the above preparation method.

[0017] Beneficial effects: The present invention utilizes di(3,6-diaminocarbazole)dimethylsilane containing four amino groups and toluene-2,4-diisocyanate to carry out polymerization reaction to generate a polyurea polymer with a three-dimensional network structure. After high-temperature carbonization, the obtained carbon-based high-temperature and high-rate lithium battery negative electrode material has a large number of pore structures and exhibits a higher specific surface area. During the charge and discharge process, it can provide more migration and transmission channels and lithium storage sites for lithium ions, thereby exhibiting a higher specific capacity.

[0018] The molecular chain of the polyurea polymer of the present invention contains carbazole-based nitrogen-containing pyrrole heterocycles and silicon elements. During the high-temperature carbonization process, the nitrogen-containing pyrrole heterocycles are pyrolyzed to form active nitrogen doping structures such as pyrrole nitrogen and graphite nitrogen, which are beneficial to improving the electrochemical properties such as the conductivity and specific capacity of the carbon-based negative electrode material. At the same time, during the high-temperature carbonization process, the silicon element forms active components such as nano-silicon and silicon carbide, which are uniformly dispersed in the carbon matrix, further improving the electrochemical properties such as specific capacity, so that the negative electrode material exhibits higher charge and discharge specific capacity, coulomb efficiency and rate performance, and at a high temperature of 60°C, still exhibits good first charge and discharge specific capacity and coulomb efficiency. DETAILED DESCRIPTION

[0019] In order to make the purpose, technical scheme and advantages of the embodiments of the present application clearer, the technical scheme in the embodiments of the present application will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or the conditions recommended by the manufacturer. The reagents or instruments used without indicating the manufacturer are all conventional products that can be purchased commercially. Palladium carbon catalyst: palladium content 10%, Hubei Langbowan Biomedicine Co., Ltd.

[0020] Embodiment 1:

[0021] (1) Add 200 mL of tetrahydrofuran solvent and 80 mmol of 3,6-dinitro-9H-carbazole (CAS registration number 3244-54-0) to a reaction container in a low-temperature reactor, add a n-hexane solution containing 104 mmol of n-butyl lithium (molar concentration of 2.5 mol / L) dropwise at -78°C, stir and activate for 2 hours, then add 40 mmol of dichlorodimethylsilane (CAS registration number 75-78-5) dropwise, react at room temperature for 18 hours, rotary evaporate, wash with methanol, add the product to 250 mL of ethanol, add 0.12 g of palladium carbon catalyst and 16 mL of 80% hydrazine hydrate solution, heat to 85°C, condense and reflux for 5 hours, filter and rotary evaporate, separate by silica gel column chromatography, and gradient elute with ethyl acetate and petroleum ether eluent to obtain di(3,6-diaminocarbazole)dimethylsilane.

[0022] (2) Add 300 mL of N,N-dimethylformamide, 30 mmol of di(3,6-diaminocarbazole)dimethylsilane, 120 mmol of toluene-2,4-diisocyanate, and 0.8 mmol of dibutyltin dilaurate into a reaction container, heat to 75° C., stir and react for 4 hours, add water to the solution, filter, wash with ethanol, and dry to obtain a silicon-containing polyurea polymer.

[0023] (3) 10 g of silicon-containing polyurea polymer was ground and crushed, mixed with 30 g of potassium hydroxide, and placed in a tubular furnace. Nitrogen was introduced and the temperature was increased to 850° C. at a heating rate of 5° C. / min. The mixture was carbonized for 3 h. After cooling, the mixture was ground and crushed, washed with water, and dried to obtain a negative electrode material for a high-temperature and high-rate lithium battery.

[0024] Embodiment 2:

[0025] (1) Add 250 mL of tetrahydrofuran solvent and 96 mmol of 3,6-dinitro-9H-carbazole to a reaction container in a low-temperature reactor, add a n-hexane solution containing 128 mmol of n-butyl lithium (molar concentration of 2.5 mol / L) dropwise at -78°C, stir and activate for 3 hours, then add 40 mmol of dichlorodimethylsilane dropwise, react at room temperature for 12 hours, rotary evaporate, wash with methanol, add the product to 250 mL of ethanol, add 0.15 g of palladium carbon catalyst and 20 mL of 80% hydrazine hydrate solution, heat to 75°C, condense and reflux for 8 hours, filter and rotary evaporate, separate by silica gel column chromatography, and gradient elute with ethyl acetate and petroleum ether eluent to obtain di(3,6-diaminocarbazole)dimethylsilane.

[0026] (2) Add 400 mL of N,N-dimethylformamide, 30 mmol of di(3,6-diaminocarbazole)dimethylsilane, 120 mmol of 4,4'-methylenebis(phenyl isocyanate), and 0.9 mmol of dibutyltin dilaurate into a reaction container, heat to 65°C, stir and react for 5 hours, add water to the solution, filter, wash with ethanol, and dry to obtain a silicon-containing polyurea polymer.

[0027] (3) 10 g of silicon-containing polyurea polymer was ground and crushed, mixed with 25 g of potassium hydroxide, and placed in a tubular furnace. Nitrogen was introduced and the temperature was increased to 900° C. at a heating rate of 10° C. / min. The mixture was carbonized for 3 h. After cooling, the mixture was ground and crushed, washed with water, and dried to obtain a negative electrode material for a high-temperature and high-rate lithium battery.

[0028] Embodiment 3:

[0029] (1) Add 400 mL of N,N-dimethylformamide, 30 mmol of di(3,6-diaminocarbazole)dimethylsilane (prepared in Example 1), 126 mmol of toluene-2,4-diisocyanate, and 0.8 mmol of dibutyltin dilaurate into a reaction container, heat to 60° C., stir and react for 5 h, add water to the solution, filter, wash with ethanol, and dry to obtain a silicon-containing polyurea polymer.

[0030] (2) 10 g of silicon-containing polyurea polymer was ground and pulverized, mixed with 25 g of potassium hydroxide, and placed in a tubular furnace. Nitrogen was introduced and the temperature was increased to 950° C. at a heating rate of 5° C. / min. The mixture was carbonized for 2 h. After cooling, the mixture was ground and pulverized, washed with water, and dried to obtain a negative electrode material for a high-temperature and high-rate lithium battery.

[0031] Embodiment 4:

[0032] (1) Add 300 mL of N,N-dimethylformamide, 30 mmol of bis(3,6-diaminocarbazole)dimethylsilane (prepared in Example 1), 114 mmol of 4,4'-methylenebis(phenyl isocyanate), and 0.8 mmol of dibutyltin dilaurate into a reaction container, heat to 65° C., stir and react for 5 h, add water to the solution, filter, wash with ethanol, and dry to obtain a silicon-containing polyurea polymer.

[0033] (2) 10 g of silicon-containing polyurea polymer was ground and crushed, mixed with 40 g of potassium hydroxide, and placed in a tubular furnace. Nitrogen was introduced and the temperature was increased to 850° C. at a heating rate of 5° C. / min. The mixture was carbonized for 3 h. After cooling, the mixture was ground and crushed, washed with water, and dried to obtain a negative electrode material for a high-temperature and high-rate lithium battery.

[0034] Embodiment 5:

[0035] (1) Add 350 mL of N,N-dimethylformamide, 30 mmol of bis(3,6-diaminocarbazole)dimethylsilane (prepared in Example 1), 114 mmol of 4,4'-methylenebis(phenyl isocyanate), and 0.6 mmol of dibutyltin dilaurate into a reaction container, heat to 75° C., stir and react for 3 h, add water to the solution, filter, wash with ethanol, and dry to obtain a silicon-containing polyurea polymer.

[0036] (2) 10 g of silicon-containing polyurea polymer was ground and crushed, mixed with 30 g of potassium hydroxide, and placed in a tubular furnace. Nitrogen was introduced and the temperature was increased to 900° C. at a heating rate of 5° C. / min. The mixture was carbonized for 3 h. After cooling, the mixture was ground and crushed, washed with water, and dried to obtain a negative electrode material for a high-temperature and high-rate lithium battery.

[0037] Comparative Example 1

[0038] (1) Add 300 mL of N,N-dimethylformamide and 30 mmol of 3,6-diaminocarbazole (CAS No. 86-71-5, structural formula: ), 120 mmol toluene-2,4-diisocyanate, 0.8 mmol dibutyltin dilaurate, heated to 75°C, stirred for reaction for 4 hours, water was added to the solution, filtered, washed with ethanol, and dried to obtain a polyurea polymer.

[0039] (2) 10 g of polyurea polymer was ground and crushed, mixed with 30 g of potassium hydroxide, and placed in a tubular furnace. Nitrogen was introduced and the temperature was increased to 850° C. at a heating rate of 5° C. / min. The mixture was carbonized for 3 h. After cooling, the mixture was ground and crushed, washed with water, and dried to obtain a negative electrode material for a high-temperature and high-rate lithium battery.

[0040] Comparative Example 2

[0041] (1) Add 300 mL of N,N-dimethylformamide and 30 mmol of bis(4-aminophenoxy)dimethylsilane (CAS No. 1223-16-1, structural formula: ), 120 mmol toluene-2,4-diisocyanate, 0.8 mmol dibutyltin dilaurate, heated to 75°C, stirred for reaction for 4 hours, water was added to the solution, filtered, washed with ethanol, and dried to obtain a silicon-containing polyurea resin.

[0042] (2) Grind 10 g of silicon-containing polyurea resin, mix with 30 g of potassium hydroxide and place in a tubular furnace. Pass nitrogen and heat to 850 °C at a heating rate of 5 °C / min. Carbonize for 3 h. Grind after cooling, wash with water and dry to obtain a negative electrode material for a high-temperature and high-rate lithium battery.

[0043] The total specific surface area of ​​the negative electrode material for high-temperature and high-rate lithium batteries was tested by a fully automatic specific surface area and porosity analyzer. The test results are shown in Table 1.

[0044] Table 1: Specific surface area

[0045] <![CDATA[Total specific surface area (m 2 / g)]]> Example 1 782.1 Example 2 833.7 Example 3 730.8 Example 4 865.2 Example 5 819.2 Comparative Example 1 623.9 Comparative Example 2 416.5

[0046] Table 1 shows that the specific surface area of ​​the negative electrode materials for high temperature and high rate lithium batteries of Examples 1-5 is 730.8-865.2 m 2 / g, this is because bis(3,6-diaminocarbazole)dimethylsilane contains four amino polymerization sites. After polymerization reaction with diisocyanate, it generates a polyurea polymer with a three-dimensional network structure. After high-temperature carbonization, the obtained carbon material has more porous structure and larger specific surface area.

[0047] The 3,6-diaminocarbazole in Comparative Example 1 and the bis(4-aminophenoxy)dimethylsilane in Comparative Example 2 have fewer amino polymerization sites, making it difficult to generate polyurea polymers with a three-dimensional network structure. The carbon materials have fewer pore structures and lower specific surface areas after high-temperature carbonization.

[0048] The negative electrode material of high-temperature and high-rate lithium battery, the conductive agent acetylene black, and the binder polyvinylidene fluoride were added to N-methylpyrrolidone in a mass ratio of 8:1:1. After stirring, the slurry was coated on the surface of copper foil and dried to make the negative electrode. The metal lithium tail positive electrode and glass fiber membrane were used as the diaphragm. The 1 mol / L lithium hexafluorophosphate solution was used as the electrolyte, and the solvent was ethylene carbonate and dimethyl carbonate in a volume ratio of 1:1. The button cell was formed in an argon glove box. The Land CT2001A battery test system was used for electrochemical performance testing, with a voltage range of 0.01-3.0V. The test temperature was 25-60℃.

[0049] The button cell was tested for specific capacity at current densities of 100mA / g, 200mA / g, 500mA / g, and 1000mA / g, respectively, and the test temperature was 25°C; then the specific capacity was tested again at a current density of 100mA / g. The specific capacities C1 and C2 at 100mA / g were compared with the first and second times. The test results are shown in Table 2-3.

[0050] Table 2: Specific capacity

[0051]

[0052] Table 3: Current density

[0053]

[0054]

[0055] Tables 2 and 3 show that the first and second specific capacities C1 and C2 of Examples 1-5 are very high at 100 mA / g, and the rate performance is very good. In addition, at 25°C and high temperature 60°C, they all have higher first charge and discharge specific capacities and high coulombic efficiency. This is because the prepared high-temperature and high-rate lithium battery negative electrode material has higher porosity and specific surface area, and can provide more migration and transmission channels and lithium storage sites for lithium ions during the charge and discharge process, thereby showing a higher specific capacity. At the same time, the molecular chain of the polyurea polymer contains carbazole-based nitrogen-containing pyrrole heterocycles and silicon elements. During the high-temperature carbonization process, the nitrogen-containing pyrrole heterocycles are pyrolyzed to form active nitrogen-doped structures such as pyrrole nitrogen and graphite nitrogen, which is beneficial to improve the electrochemical properties such as the conductivity and specific capacity of the carbon-based negative electrode material. At the same time, during the high-temperature carbonization process, silicon elements form active ingredients such as nano-silicon and silicon carbide, which are evenly dispersed in the carbon matrix, further improving the electrochemical properties such as specific capacity, making the negative electrode material exhibit higher charge and discharge specific capacity, coulombic efficiency and rate performance, and at a high temperature of 60°C, it still exhibits good first charge and discharge specific capacity and coulombic efficiency.

[0056] In Comparative Example 1, 3,6-diaminocarbazole and toluene-2,4-diisocyanate are used for polymerization reaction. The obtained polyurea polymer does not contain silicon element, and high-temperature carbonization does not form active ingredients such as nano-silicon and silicon carbide in the carbon matrix. In addition, the specific surface area of ​​the carbon-based negative electrode material is small, resulting in low charge and discharge specific capacity, coulomb efficiency and rate performance of the composite material.

[0057] In Comparative Example 2, bis(4-aminophenoxy)dimethylsilane and toluene-2,4-diisocyanate are used for polymerization reaction. The obtained polyurea polymer does not contain carbazole-based nitrogen-containing pyrrole heterocycles. After high-temperature carbonization, there are very few active nitrogen doping structures such as pyrrole nitrogen and graphitic nitrogen in the carbon matrix, resulting in low charge and discharge specific capacity, coulomb efficiency and rate performance of the composite material.

[0058] The embodiments described above are part of the embodiments of the present application, rather than all of the embodiments. The detailed description of the embodiments of the present application is not intended to limit the scope of the present application for protection, but merely represents the selected embodiments of the present application. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work belong to the scope of protection of the present application.

Claims

1. A method for preparing a negative electrode material for a high-temperature and high-rate lithium battery, characterized in that: The preparation method comprises the following steps: S1, adding N,N-dimethylformamide, di(3,6-diaminocarbazole)dimethylsilane, diisocyanate, and dibutyltin dilaurate into a reaction container, stirring for reaction, adding water to the solution, filtering, washing, and drying to obtain a silicon-containing polyurea polymer; S2. Grind and crush the silicon-containing polyurea polymer, mix it with potassium hydroxide, place it in a tubular furnace, introduce nitrogen gas to carbonize it, grind and crush it after cooling, wash it, and dry it to obtain a negative electrode material for a lithium battery for high temperature and high rate use.

2. The method for preparing a negative electrode material for a high temperature and high rate lithium battery according to claim 1, characterized in that: The ratio of the bis(3,6-diaminocarbazole)dimethylsilane, diisocyanate and dibutyltin dilaurate is 1 mol:(3.8-4.2) mol:(0.02-0.03) mol.

3. The method for preparing a negative electrode material for a high temperature and high rate lithium battery according to claim 2, characterized in that: The diisocyanate is toluene-2,4-diisocyanate or 4,4'-methylenebis(phenyl isocyanate).

4. The method for preparing a negative electrode material for a high temperature and high rate lithium battery according to claim 1, characterized in that: The reaction temperature in S1 is 60-75°C and the reaction time is 3-5h.

5. The method for preparing a negative electrode material for a high temperature and high rate lithium battery according to claim 1, characterized in that: The carbonization process in S2 is to heat up to 850-950°C at a heating rate of 5-10°C / min and keep the temperature for 2-3h.

6. The method for preparing a negative electrode material for a high temperature and high rate lithium battery according to claim 1, characterized in that: The ratio of the silicon-containing polyurea polymer to potassium hydroxide in S2 is 1 g:(2.5-4) g.

7. The method for preparing a negative electrode material for a high temperature and high rate lithium battery according to claim 1, characterized in that: The preparation method of the bis(3,6-diaminocarbazole)dimethylsilane comprises the following steps: adding a solvent and 3,6-dinitro-9H-carbazole into a reaction container, dripping an n-hexane solution of n-butyl lithium, stirring and activating for 2-3 hours, then dripping dichlorodimethylsilane, reacting at room temperature for 12-18 hours, rotary evaporating, washing, adding the product into ethanol, adding a palladium carbon catalyst and a hydrazine hydrate solution, heating to 75-85° C., condensing and refluxing for 5-8 hours, filtering, rotary evaporating, and separating by silica gel column chromatography to obtain the bis(3,6-diaminocarbazole)dimethylsilane.

8. The method for preparing a negative electrode material for a high temperature and high rate lithium battery according to claim 7, characterized in that: The ratio of the 3,6-dinitro-9H-carbazole, n-butyl lithium and dichlorodimethylsilane is (2-2.4) mol: (2.6-3.2) mol: 1 mol.

9. The method for preparing a negative electrode material for a high temperature and high rate lithium battery according to claim 7, characterized in that: The solvent is tetrahydrofuran or toluene.

10. A negative electrode material for a high-temperature and high-rate lithium battery prepared according to the preparation method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • A method for preparing carbon-coated silicon anode materials assisted by boron-nitrogen doped polymers

    CN110752352B

  • Preparation method of polyurea-based carbon-coated carbon fluoride cathode material

    CN105185959A

  • Polyurea derived functional carbon and preparation method and application thereof

    CN111252752A

  • Preparation method of binder for lithium battery

    CN111682213A

  • Siloxane-based coatings containing polymers with urea linkages and terminal alkoxysilanes

    US20170183534A1